2018
DOI: 10.1016/j.irbm.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Sound Recognition at Home Using GMM

Abstract: Aiming for autonomous living for the people after a stroke is the challenge these days especially for swallowing disorders or dysphagia. It is in this context that the e-swallhome project proposes to develop tools, from hospital care until the patient returns home, which are able to monitor in real time the process of swallowing. This paper proposes a non-invasive acoustic based method to differentiate between swallowing sounds and other sounds in normal ambient environment during food intake. Gaussian Mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A model including MFCC features, in particular, demonstrated good performance. The MFCC is a feature that is widely used for voice recognition [30,31] and for identifying swallowing sounds [23,36]. In this study, feature patterns using the MFCC as the basis showed the most superior performance.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A model including MFCC features, in particular, demonstrated good performance. The MFCC is a feature that is widely used for voice recognition [30,31] and for identifying swallowing sounds [23,36]. In this study, feature patterns using the MFCC as the basis showed the most superior performance.…”
Section: Discussionmentioning
confidence: 86%
“…Advances in machine learning confer the possibility of further improvement of accuracy when detecting swallowing sounds [22][23][24][25]. Khlaifi et al combined the Mel Frequency Cepstral Coefficient (MFCC) and a Gaussian Mixture Model (GMM) to achieve an 84.57% recognition rate [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation at the inspiratory-expiratory transition is ensured by these pI neurons in the pontine Kölliker-Fuse nucleus, providing an eupneic inspiratory-expiratory transition; pI neurons start the post-inspiratory vagal nerve activity, when they are no more inhibited by the early inspiratory neurons eI: that occurs when eI neurons (which have a constant basal activity) are inhibited by the expiratory E neurons, these last being triggered by eI neurons and by the decrease of the pI neurons inhibition. The role of swallowing is partly unknown but the loss of the swallowing reflex after a brain stroke provokes a dyspneic breathing [3,24].…”
Section: 1mentioning
confidence: 99%
“…GMM is a linear weighted combination of a certain number of Gaussian probability density functions. The probability density function of an N-order GMM is a linear combination of N single Gaussian distributions, which is used to describe the distribution of frame features in the feature space [33], as shown in (11).…”
Section: Sound Trainingmentioning
confidence: 99%